Effects of seafood consumption on mercury exposure in Norwegian pregnant women: A randomized controlled trial. (August 2020) - Næss, Synnøve; Kjellevold, Marian; Dahl, Lisbeth; Nerhus, Ive; Midtbø, Lisa Kolden; Bank, Michael S.; Rasinger, Josef D.; Markhus, Maria Wik
Highlights: Mercury (Hg) hair concentrations in pregnant women were measured before and after a 16-week cod intervention. Hg hair concentrations were generally low in both the control and intervention group. The intervention increased hair Hg slightly but did not increase the number of subjects exceeding the US EPA reference dose. Women with lower Hg hair concentrations were more affected by the intervention. Hg exposure during the intervention was below the EFSA tolerable weekly intake advice. Abstract: Background: Seafood provides nutrients that are important for optimal development of the unborn child. However, seafood is also a source of contaminants including mercury (Hg) and methylmercury (MeHg) that may have adverse effects on neurodevelopment of the fetus. Humans are predominantly exposed to MeHg through seafood consumption, however, levels of MeHg vary considerably between species. Objectives: Investigate, in a randomized controlled trial (RCT) during pregnancy, if an increased intake of Atlantic cod ( Gadus morhua ), a fish species with relatively low levels of MeHg contamination, influences total hair Hg (THHg) concentrations in humans. Methods: Pregnant women ( n  = 137) were enrolled in the RCT "Mommy's Food" (2016–2017), which was designed to increase iodine status. Participants were randomly assigned to intervention (400 g of cod fillets per week) or control (continued habitual diet) groups for 16 weeks (gestational week 20–36). THHg concentrations were measured at baseline and post-intervention using thermal decomposition, amalgamation, and atomic absorption spectrophotometry (US EPA method 7473). The trial is registered in ClinicalTrials.gov, NCT02610959. Results: Post-intervention, the intervention group had median (inter-quartile range) THHg concentrations of 554 (392–805) µg/kg, and the control group 485 (341–740) µg/kg ( p  = 0.186). When adjusting for baseline THHg concentrations, there was a significant difference between the groups in those participants with baseline THHg concentrations below 534 µg/kg. Post-intervention, 8% of the study population exceeded the US EPA reference dose in hair (1, 000 µg/kg) (intervention group: n  = 6, control group: n  = 4). Conclusion: THHg concentrations were generally low in both study groups of pregnant women, despite the relatively high seafood intake. While the intervention with 400 g of cod per week slightly increased THHg concentrations, it did not lead to an increase in number of subjects exceeding the US EPA reference dose; a dose level at which no adverse effects are expected to occur over a period of lifetime exposure.